Morbidity and mortality after recognition of macroalbuminuria in Pasifika people with type 2 diabetes in a primary health-care practice - Tim Cundy; Glenn Doherty; Fifita McCready; Tian Cooke (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONMacroalbuminuria in people with type 2 diabetes is common among Pasifika peoples and is associated with end-stage kidney disease and major cardiovascular disease. AIMIn a primary care practice catering for Pasifika people, to determine the time after first recognition of macroalbuminuria to the occurrence of major cardiovascular and renal events, and to examine the relationship with retinopathy status. METHODSIn a retrospective observational cohort study, we documented the occurrence of major cardiovascular events and amputations, end-stage kidney disease and death in 115 people with type 2 diabetes reviewed by a specialist diabetes physician at the Langimalie Tongan Health practice between 2005 and 2018. The follow up was 1-19 (median 9.5) years from the first recognition of macroalbuminuria (albumin:creatinine ratio of >30g/mol). Survival was described by using Kaplan-Meier analysis. RESULTSMacroalbuminuria was detected a mean of 9 years after the diagnosis of diabetes, at a mean age of 52 (standard deviation 12) years. Within 6 years of macroalbuminuria detection, 4% of people had died, 15% had reached end-stage kidney disease, 15% had cardiovascular events or amputations and 30% had the composite outcome of any of these. Within 12 years, the respective proportions were: 24%, 29%, 20% and 48%. The composite outcome was less frequent (P<0.002) in patients without retinopathy at the time macroalbuminuria was recognised. Compared to patients with retinopathy, this group were younger (P=0.025), more obese (P<0.0001), had better baseline renal function (P=0.018) and a shorter interval between the diagnosis of diabetes and recognition of macroalbuminuria (P<0.0001). DISCUSSIONIn this Pasifika population, macroalbuminuria was a marker for serious adverse cardiovascular and renal disease, and mortality, but in the 29% of patients without retinopathy at the time of recognition of macroalbuminuria, the natural history was more benign. The management of such comorbid patients is a substantial challenge for primary health-care services.